Tweed - Anderson, Fiona, 1985- (London : Bloomsbury Academic, 2017)
"The story of tweed is tied to a series of social, economic and cultural shifts that have molded its development. This book considers the historical factors that helped to shape the characteristics and social meanings of the group of fabrics that we call tweed since their emergence in the 1820s to the present day. Including significant new research on tweeds, from Harris Tweed to the type used by Chanel, this book follows the history of these fabrics from the raw fibre to the finished garment in men's and women's fashion. Exploring rural and urban contexts, Anderson shows that, contrary to their strong popular associations with tradition, tweeds emerged in the Romantic era as a response to the dramatic changes associated with industrialisation and urbanisation. Progressive changes in gender relations are also explored as a major factor in tweed's evolution from associations with particular ideals of masculinity into what is now a truly contemporary and adaptable fashion textile worn by both sexes. This is the first book of its kind to recognize the versatility of tweed and its importance in textiles and fashion today. "--
Machine generated contents note: -- List of Illustrations -- Acknowledgements 1. Introduction -- 2. Tweed: Terms, Descriptions and Characteristics -- 3. Origins and Early Development of Tweed to 1850 -- 4. Tweed, Male Fashion and Modern Masculinities 1851-1918 -- 5. Tweed, Femininity and Fashion 1851-1918 -- 6. Suits You: Men and Tweed 1919-1952 -- 7. Sportswear Chic: Tweed in Womenswear 1919 to 1952 -- 8. Couture to Pop and Nostalgic Fashion: 1953 to 1980 -- 9. Tradition and Innovation: 1981 to 2014 Bibliography -- Index.
Includes bibliographical references and index.
Keywords: Clothing and dress -- Social aspects; DESIGN / History & Criticism; DESIGN / Textile & Costume; Fashion -- Social aspects; Tweed -- History